PENGGUNAAN MINYAK SAWIT UNTUK SUBSTITUSI LEMAK SUSU DALAM PRODUKSI SUSU KENTAL MANIS - Naruki, Sri; Marsono, Yustinus; Murdiati, Agnes (Widya Mandala Surabaya Catholic University, 2004)
A research on substitution of milk fat with palm oil in Sweet Condense Milk (SCM) production has been conducted. The aim of this research was to investigate the effects of milk fat substitution with palm oil on physical, chemical and nutritional properties of the Palm Oil SCM (POSCM) POSCM were prepared by substitution of corn oil (0, 25, 50, 75 and 100%) with palm oil (R-vita) of the commercial recombined SCM formula. Chemical and physical properties of the POSCMs were determined. The POSCMs were then reconstituted and sensory character as well as nutritional properties was examined. The result showed that substitution of 50% corn oil with red palm oil (R-vita)resulted in a good quality of POSCM similar to the control SCM (0% red palm oil). This POSCM have viscosity and chemical composition similar to SCM and the emulsion stability 98%. POSCM production decreased 10% of carotene content but the tocoferol content were not affected bu the process. Substitution of milk fat with red palm oil decrease the cholesterol but have no effects on TAG concentration in rats.